2021
DOI: 10.1111/aab.12731
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and salicylic acid function synergistically to promote the drought resilience through upregulation of antioxidant profile for enhancing potassium use efficiency and wheat yield

Abstract: Inducing tolerance against drought stress with plant growth regulator and plant nutrients is vital for ensuring food security and sustainable crop production. The present study was undertaken to assess the influence of salicylic acid (SA) either seed primed or foliar application (1.1, 2.2, 0.7 and 1.4 mM SA) coupled with potassium (K) fertilisation (0, 50 and 100 kg/ha) on wheat yield and nutrients uptake under drought stress (100% field capacity [FC], 60% FC, 30% FC) at tillering stage. Findings revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Wheat plants which were irrigated every 6 days and sprayed with 300 ppm salicylic acid gained the highest mean values of flag leaf area (69.5 cm 2 ) in the 2 nd season, kernels weight spike -1 (4.9 g), and 1000-grain weight (70.5 g) in the 1 st season., while the interaction between I 12 ×SA 1 recorded the lowest value for these traits, and the highest value for WUE (0.73 kg m 3 ) was attained from (I 12 ×SA 3 ) in the 2 nd season. Our results are in harmony with those acquired by Sofy (2015), El-Saadony et al (2021) and Munsif et al (2022).…”
Section: Interaction Effectsupporting
confidence: 92%
See 4 more Smart Citations
“…Wheat plants which were irrigated every 6 days and sprayed with 300 ppm salicylic acid gained the highest mean values of flag leaf area (69.5 cm 2 ) in the 2 nd season, kernels weight spike -1 (4.9 g), and 1000-grain weight (70.5 g) in the 1 st season., while the interaction between I 12 ×SA 1 recorded the lowest value for these traits, and the highest value for WUE (0.73 kg m 3 ) was attained from (I 12 ×SA 3 ) in the 2 nd season. Our results are in harmony with those acquired by Sofy (2015), El-Saadony et al (2021) and Munsif et al (2022).…”
Section: Interaction Effectsupporting
confidence: 92%
“…The grain yield increase was related to the improvement of most agronomic traits that correlated with grain yield, in response to short irrigation intervals (Aissaoui and Fenni, 2021). Many researchers reported that shorter irrigation intervals improved the growth and yield traits of wheat crops (Shah et al, 2016;Ragheb et al, 2017;Ahmed and Mustafa, 2018;Walsh et al, 2020;Munsif et al, 2022). Increasing irrigation period was followed by a significant decrease in all studied traits except for protein under sandy soils conditions, which leads to rapid loss of water and nutrients, and exposes plants to drought stress, thus an increase in protein content of wheat plants (El-Saadony et al, 2021).…”
Section: Effect Of Irrigation Intervalsmentioning
confidence: 99%
See 3 more Smart Citations